Analisis Tulisan Tangan Melalui Grafologi pada Mahasiswa Psikologi Universitas Sahid Surakarta - Yuliana Setyaningrum; Anniez Rachmawati Musslifah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Graphology is a science that studies a person's personality and character through handwriting. This activity aims to introduce Sahid University Surakarta students to graphological analysis methods as a tool for understanding themselves and others. This seminar was conducted as part of a community service program, with a target audience of students and the general public. The method used in this service is the lecture method. The resource person also uses lecture and practice methods which are more effective and can be used in the community service process. The results of the activity showed that participants gained new insights into their potential and practical techniques to improve interpersonal understanding.